Impact of Extracorporeal Membrane Oxygenation on Right Ventricular Function After Heart Transplantation - Zhao, Cheng; Hao, Xing; Xue, Chao; Zhao, Yichen; Han, Jie; Jia, Yixin; Hou, Xiaotong; Wang, Jiangang (Frontiers in Cardiovascular Medicine, 2022)
Aims Acute right ventricular failure remains a common challenging clinical syndrome in heart transplant (HTx) recipients. While extracorporeal membrane oxygenation (ECMO) is a proven strategy for the treatment of this condition, the outcomes after weaning and during follow up remain understudied. We aimed to evaluate the right-sided heart function in ECMO survivors following HTx. Methods Between September 2005 and December 2019, 205 patients with end-stage heart failure who underwent standard orthotopic HTx were enrolled. In total, 68 (33.2%) patients were included in the ECMO group and 137 (66.8%) patients were included in the non-ECMO group. Results Of the 68 patients in the ECMO group, 42 (61.8%) were successfully weaned from ECMO. After a median follow-up period of 53 months, there were 25 (59.5%) and 27 (23.7%) deaths in the ECMO and non-ECMO groups (P = 0.023), respectively. Systolic pulmonary artery pressure (SPAP) before discharge (P = 0.003) was the unique predictor of all-cause mortality during follow up. Meanwhile, patients in the ECMO group with more than moderate SPAP increase before discharge had higher mortality than patients in the non-ECMO group without such increase (P = 0.005). Conclusions Recipient right-sided heart characteristics were strong predictors of ECMO need after HTx. ECMO patients had high mortality in the perioperative and follow-up periods, and the changes in right ventricular function in ECMO patients may be associated with pulmonary vessel injury before and after HTx.